-8(x-1)=6
como se resolv
Soluções para a tarefa
Respondido por
0
Oi,
Resolução
-8(x-1)=6
- 8x + 8 = 6
- 8x = 6 - 8
- 8x = - 2 . (-1)
8x = 2
x = 2/8
x = 1/4
Espero ter ajudado e bons estudos !
Resolução
-8(x-1)=6
- 8x + 8 = 6
- 8x = 6 - 8
- 8x = - 2 . (-1)
8x = 2
x = 2/8
x = 1/4
Espero ter ajudado e bons estudos !
Respondido por
0
-8(x-1)=6
-8x +8 = 6
-8x= 6 -8
-8x= -2 . (-1)
8x= 2
x= 2/8
x= 0,25
Bons estudos!
-8x +8 = 6
-8x= 6 -8
-8x= -2 . (-1)
8x= 2
x= 2/8
x= 0,25
Bons estudos!
Perguntas interessantes
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás